2011
DOI: 10.1016/j.watres.2011.04.029
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring of water quality from roof runoff: Interpretation using multivariate analysis

Abstract: The quality of harvested rainwater used for toilet flushing in a private house in the south-west of France was assessed over a one-year period. Temperature, pH, conductivity, colour, turbidity, anions, cations, alkalinity, total hardness and total organic carbon were screened using standard analytical techniques. Total flora at 22 °C and 36 °C, total coliforms, Escherichia coli and enterococci were analysed. Overall, the collected rainwater had good physicochemical quality but did not meet the requirements for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
60
1
12

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 135 publications
(81 citation statements)
references
References 42 publications
8
60
1
12
Order By: Relevance
“…The strong acidity of well waters around the sites is in contrast to a previous study conducted in Guinea where the pH content was skewed to be alkaline [13]. Our findings for pH is firmly in line with a similar in Bo, Sierra Leone [9], and recently reported for ground water sources around a Dumpsite Lagos, Nigeria [14]; and in bacteriological contamination of shallow ground water in Cameroon [15]; and surface runoff even though the studies were slightly different [16]. Probable reason for such strong acid nature at these sites could be ascribed to the surrounding coastal water which is controlled by its hydrological settings [14].…”
Section: Resultssupporting
confidence: 89%
“…The strong acidity of well waters around the sites is in contrast to a previous study conducted in Guinea where the pH content was skewed to be alkaline [13]. Our findings for pH is firmly in line with a similar in Bo, Sierra Leone [9], and recently reported for ground water sources around a Dumpsite Lagos, Nigeria [14]; and in bacteriological contamination of shallow ground water in Cameroon [15]; and surface runoff even though the studies were slightly different [16]. Probable reason for such strong acid nature at these sites could be ascribed to the surrounding coastal water which is controlled by its hydrological settings [14].…”
Section: Resultssupporting
confidence: 89%
“…Exclusion of this PF5 for WWTP2 meant the reduction in the explained variance from 71.22% down to 63.82% of the dataset. Similar results have been previously reported; Zhang et al [7] reported an explained variance of 58.79% for four factors controlling the water quality of the Xiangjiang River, and Vialle et al [8] explained, with three components, a 60.00% of the total variance of their dataset for water quality monitoring of roof runoff.…”
Section: Principal Factor Analysis For Wwtp2supporting
confidence: 88%
“…The final objective was to investigate a data reduction that allows grouping water quality variables into selected factors with common features to describe the behaviour of the plant in terms of pollution sources and treatment efficiency with a few uncorrelated components. Multivariate techniques have been widely applied to grouping water quality variables for different purposes; i.e., the composition of sewage of domestic origin [5], surface water [6,7], water quality from roof runoff [8], river watersheds [9], distribution of organic pollutants [10,11], heavy metal distribution in waters [12], new policy instruments in domestic wastewater treatment systems [13], mineral waters [14], and WWTP [15][16][17], among others. The multivariate statistical analysis employed for this study, besides allowing us to simplify the whole set of analyzed variables, eventually gave unexpected relationships among data, leading us to extract conclusions never expected with a more simplistic statistical approach [18].…”
Section: Introductionmentioning
confidence: 99%
“…O crescimento populacional e o uso e ocupação do solo de forma desordenada limita a disponibilidade de água para usos múltiplos (VIALLE et al, 2011). Esse fato é mais agravante em regiões secas onde a limitação da disponibilidade hídrica é um processo natural.…”
Section: Introductionunclassified